Introduction and Preservation of Cultural Heritage Along the Kapuas River in Pontianak for History Teachers and Students - Mohammad Rikaz Prabowo; Andang Firmansyah; Ika Rahmatika Chalimi; Haris Firmansyah; Astrini Eka Putri; Edwin Mirzachaerulsyah (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
History learning requires teachers to contextualize the material by utilizing the environment where students live as interrelated learning material. For example, with its historical journey, integrating the potential of natural wealth in Pontianak, such as the Kapuas River, can be used for educational purposes. Community service activities aim to introduce past cultural heritage, most of which is located around the banks of the Kapuas River. There were 32 participants in this activity, consisting of teachers and students. Through this activity, it is hoped that teachers will have an overview of cultural heritage, which can be used as a historical learning resource to contextualize or link to learning material. The method used is Participatory Action Research (PAR), which involves providing materials and visits to cultural heritage sites to provide participants with an overview of the history of Pontianak and its cultural heritage. Among others are the Pontianak Sultanate area, namely the Kadriyah Palace and the Jami Mosque. Visitors can build communication and get material directly from resource persons on duty at the location. The activity results showed that after visiting one of the locations, participants felt emotional closeness and actively explored independently, building discussions with resource persons to enrich their knowledge. Participants also felt satisfied with the information provided by the resource person, thereby increasing their knowledge and insight about the cultural heritage on the banks of the Kapuas River, Pontianak. As evaluation material, this activity can be held again with a different theme and include more literature related to the sites visited.